For Public Communication: Promises and Perils of Public Engagement - Downey, John (Javnost-The Public, 2017)
In this article I make a case for the importance of public engagement and political commitment on the part of communication scholars. I do this initially by drawing on the work of Michael Burawoy who, in his 2004 Presidential Address to the American Sociological Association, made an impassioned argument for the rebirth of a public sociology. Burawoy’s provocation has, however, been largely overlooked by scholars working in the field of communication and media. I then discuss the impact of the Research Excellence Framework on public communication research in the United Kingdom, a development that I so far consider to be, on the whole, positive for the field of communication and media research because it has provided incentives for academics to engage with publics. However, it is crucially important to ground this public engagement in critical theory, which means that we should question the traditional dichotomy between academic and activist. The grounds for engagement in theories of reciprocity and generality have implications for what “good” and “bad” public communication research might be. Clearly, however, we need to understand who our publics are. To this end, I discuss some of the difficulties, encountered personally, in conducting critically-informed public communication research.